PENGEMBANGAN LKPD BERBASIS KOMIK UNTUK MENINGKATKAN LITERASI EKONOMI PESERTA DIDIK - Utomo, Eko Prasetyo (Jurnal Penelitian Pendidikan, 2018)
Abstract. Economic literacy or simply termed "economic literacy" is the ability to identify economic problems, the preparation of alternative solutions by considering the benefits and costs. This study aims to produce LKPD IPS based on comics to increase economic literacy in learners. This development research uses Dick, Carey, and Carey (2009) development models. Product development is piloted through formative evaluation that includes several stages: IPS material expert review, review of design experts and instructional media, one-to-one trials, small group trials, and field trials. The results of the overall evaluation, put this prototype in a very decent category. The test results show that in the field trial there is a difference of mean post test result (83.45) pre test (45.10) with significant level 0.000 0.05. t arithmetic (14.83) t table (1.701). Thus LKPD IPS based on this comic can effectively improve student learning outcomes.Â Keywords: LKPD, IPS, comics, economic literacy